Multi-modal deception detection in videos - Jin, Yibing (Nanyang Technological University, 2022)
Deception detection has much significance as it has many real-world applications. This project focuses on the verbal and visual modalities for deception detection from videos. The experiments were conducted on the most widely used dataset: Real-Life Trial. In the project, text information, visual information, and multimodal cues were considered individually for detecting deception. Moreover, this project used both machine learning and deep learning methods to obtain the best performance on this task.